Probing the attentional modulation of unconscious processing under interocular suppression in a spatial cueing paradigm. (August 2022) - Handschack, Juliane; Rothkirch, Marcus; Sterzer, Philipp; Hesselmann, Guido
Abstract: The debate about the scope and limits of unconscious visual processing under continuous flash suppression (CFS) has created a heterogeneous set of divergent findings that are yet to be reconciled. Attention has been suggested as an important factor in modulating the processing of suppressed visual information under CFS. Specifically, Eo et al. (2016) reported that semantic processing under CFS can be significantly facilitated when spatial attention is diverted away from the suppressed stimulus. Based on event-related potential (ERP) findings involving the N400, they proposed that inattention attenuates interocular suppression and thereby makes semantic processing available unconsciously, potentially reconciling conflicting evidence in the literature. In this study, we aimed to further investigate the "CFS-attenuation-by-inattention" hypothesis using functional magnetic resonance imaging (fMRI) and multivariate pattern analysis (MVPA). We tested whether the decodability of object category increases under CFS when attention is diverted away from the suppressed stimulus in a spatial cueing task. Our results provide no evidence for the "CFS-attenuation-by-inattention" hypothesis, but show higher decoding accuracies for visible stimuli than for invisible stimuli. We discuss the implications of our findings for the important endeavor of trying to reconcile the divergent reports of unconscious processing under CFS.